Design of a High Gain Compact Circular Microstrip Patch Antenna for X-Band - Patel, Madhukant; Singh Jadaun, Veerendra; Lal, Kanhiya; Kuchhal, Piyush (International Journal of Engineering and Technology, 2018)
This paper presents design a High Gain Small Size Microstrip Patch Antenna for X-Band applications such as Moving target RADAR sensor, Motion detector, Microwave camera, Ground Penetration RADAR sensors, wall penetration scanners and many medical applications. Now we have to selected circular geometry of micro strip patch antenna because circular geometry overcomes edge effect of antenna. The proposed antenna is designed to operate for X-band at the centre frequency of 10 GHz. The proposed Circular patch antenna is compact and easy to body mount with a high efficiency. The compactness makes it a better choice as compare with other antenna in the X-band. The proposed antenna shows a very sharp return loss of -46 dB at 10 GHz having narrow pattern with a good gain of 4.7 dBi. This enables its use in high directional applications. The paper represents the designing steps, and the simulation result obtained. The software used here for this circular shaped microstrip antenna is IE3D. Various parameters such as gain, power, radiation pattern, and S11 of the antenna are mentioned.